2014
DOI: 10.3103/s0095452714040100
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and immunogenetic analysis of recurrent pregnancy loss in women

Abstract: Karyotyping of 366 couples (732 individuals) with early recurrent pregnancy losses in anamnesis revealed chromosomal anomalies in 4.09% (30 cases)-within them 2.05% carry reciprocal translocations, in 0.82%-Robertsonian translocations, 0.55% carry numerical and structural gonosomal anomalies and in 0.27%-marker chromosome of unknown origin. The risk of early reproductive losses in women after exclud ing the cytogenetic component increases three fold if SNPs 1082GG, 592CC, 819CC of IL 10 gene and IFN γ + 874AT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…Several studies have identified single-nucleotide polymorphisms (SNPs) of IL-10 gene can significantly influence the levels of IL-10 production and key obstetric complications, particularly the promoter variants control IL-10 secretion [13][14][15]. Though a number of studies have been conducted to investigate the association between promoter polymorphisms of IL-10 with RPL, the results are not consistent [14][15][16][17][18][19][20][21][22][23][24]. In addition, three earlier meta-analyses yielded conflicting results regarding the association of the IL-10 promoter SNP (rs1800896: −1802A/G) with RPL [20,25,26].…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Several studies have identified single-nucleotide polymorphisms (SNPs) of IL-10 gene can significantly influence the levels of IL-10 production and key obstetric complications, particularly the promoter variants control IL-10 secretion [13][14][15]. Though a number of studies have been conducted to investigate the association between promoter polymorphisms of IL-10 with RPL, the results are not consistent [14][15][16][17][18][19][20][21][22][23][24]. In addition, three earlier meta-analyses yielded conflicting results regarding the association of the IL-10 promoter SNP (rs1800896: −1802A/G) with RPL [20,25,26].…”
Section: Introductionmentioning
confidence: 53%
“…The remaining 17 studies were full-text reviewed, and five studies were excluded, among which, one was not about recurrent abortion and not a case-control study [13], two were of unavailable genotype [32,33] and the other two were metaanalysis [25,26]. Finally, in the current study, 12 eligible case-control studies that meet the inclusion criteria were included in our meta-analysis [14,16,17,[19][20][21][22][23][24][34][35][36].…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…This investigation differs from previous meta-analyses assessing the relationship between the aforementioned polymorphisms and RPL risk performed by Medica et al [43] and Bombell et al [44] in several ways. In the present study, an extra nine studies [14][15][16][17][22][23][24][25], 1097 RPL patients, and 1192 controls were included, and additional meta-analyses were performed to examine the potential association between the −634 G/C IL-6 polymorphism and RPL. Moreover, we carried out further ethnicity-specific analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, three documents were excluded for being review articles [37][38][39]. Thus, 15 relevant studies met the inclusion criteria [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]), of which, eight were related to the IL-6 −174 G/C polymorphism and involved 859 patients and 1018 controls, four concerned the IL-6 −634 G/C polymorphism and included 343 patients and 340 controls, while six referred to the IFN-γ +874 A/T polymorphism and comprised 622 patients and 712 controls (Table 1).…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation